2016
DOI: 10.1051/0004-6361/201527236
|View full text |Cite
|
Sign up to set email alerts
|

Seeking large-scale magnetic fields in a pure-disk dwarf galaxy NGC 2976

Abstract: Aims. It is still unknown how magnetic field-generation mechanisms could operate in low-mass dwarf galaxies. Here, we present a detailed study of a nearby pure-disk dwarf galaxy NGC 2976. Unlike previously observed dwarf objects, this galaxy possesses a clearly defined disk. We also discuss whether NGC 2976 could serve as a potential source of the intergalactic magnetic field. Methods. For the purpose of our studies, we performed deep multi-frequency polarimetric observations of NGC 2976 with the VLA and Effel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…We particularly note that we focus here on the disordered component of the magnetic field, which yields the dominant contribution to the radio flux. For comparison, studies by Drzazga et al (2016) have shown that the ordered component in the outer parts of the galaxy is also affected by tidal interactions. The density of the warm neutral gas can be estimated as Σ/2H.…”
Section: Basic Assumptionsmentioning
confidence: 99%
“…We particularly note that we focus here on the disordered component of the magnetic field, which yields the dominant contribution to the radio flux. For comparison, studies by Drzazga et al (2016) have shown that the ordered component in the outer parts of the galaxy is also affected by tidal interactions. The density of the warm neutral gas can be estimated as Σ/2H.…”
Section: Basic Assumptionsmentioning
confidence: 99%
“…We believe that this scenario could be relevant to producing large-scale magnetic fields in dwarf galaxies, and potentially explain certain observations of these objects . Note that Drzazga et al (2016), when discussing observations of a dwarf galaxy NGC 2976 performed in order to isolate a large-scale magnetic pattern, discuss the necessity of a mechanism similar to that one suggested here.…”
Section: Discussionmentioning
confidence: 82%
“…This relatively low x-ray luminosity can give tighter constraints for annihilating dark matter. Furthermore, the magnetic field strength of NGC 2976 is B = 6.6 ± 1.8 µG, which is relatively higher than the local group dwarf galaxies (B = 4.2 ± 1.8 µG) (Drzazga et al 2016) so that the cooling rate of high-energy electrons is higher than the diffusion rate. The cooling timescale for a 1 GeV electron in NGC 2976 is t c = 1/b = 7 × 10 15 s while the diffusion timescale is…”
Section: The X-ray Constraintsmentioning
confidence: 90%
“…−15 erg cm −2 s −1 and S ≤ 1.76×10 −15 erg cm −2 s −1 respectively (Drzazga et al 2016). By using Eq.…”
Section: The Radio Constraintsmentioning
confidence: 94%